EXPERIENTIAL AESTHETICS IN VISUAL ARTS CONSUMPTION: FANTASY, EMOTION, AND ENJOYMENT IN CONTEMPORARY ART EXPERIENCES - Tilak, Geetali; Anute, Nilesh; Suke, Sagar Popat; Dabade, Tanaji Dinkar; Limbore, Nilesh Vitthal; Pawar, Priyanka; Dharmadhikari, Sanjay (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Experiential aesthetics has become a key point of focus in attempting to comprehend how modern viewers approach visual arts outside of the frame of formal analysis in a way that focuses on experience, emotion, and engagement of the imagination. The paper examines the inter-relationship between fantasy, emotion, and enjoyment in determining visual art consumption as a part of contemporary art experiences. The study uses phenomenological aesthetics and cognitive-affective theories, in which the conceptualization of aesthetic engagement is an embodied process with an interpretive and emotionally situated process. Fantasy is explored as one of the most important experiential forces that allow the viewers to immerse in the story, create symbolic meaning and imaginary worlds of art, creating their own meanings and speculative worlds as they engage with works of art. The paper also examines the emotional aspects of visual art viewing, such as emotion eliciting mechanisms, empathic resonance, mood, and affective bonding, and the moderating role of cultural, social and contextual factors. Pleasure is conceptualized in the context of hedonic enjoyment and eudaimonic satisfaction and it emphasizes flow, absorption, and reflective pleasure as the keys to long-term aesthetic values and recurring interest and involvement. The paper is methodologically designed in terms of a mixed-methods approach that incorporates both qualitative interviews, observational and narrative analyses with quantitative survey instruments and psychometric modeling to produce both subjective depth and the quantifiable patterns.